Construction of integration vector for nitrogen fixing genes (nif) regulation studies of Paenibacillus macerans - Goh, Boon Poh; Zainuddin, Zafarina; Najimudin, Nazalan (Penerbit Universiti Sains Malaysia, 2004)
Nitrogen is very important to living organism because nitrogen is one of the components for proteins and nucleic acids. Nitrogen is one of the limiting factors in agriculture.